PERAN LEMBAGA PEMBERDAYAAN MASYARAKAT DALAM PEMBANGUNAN DESA MANJAPAI KECAMATAN BONTONOMPO KABUPATEN GOWA TELAAH SIYASAH SYAR’IYYAH - Wahyuni, Eka Sri; Djafar, Usman; Halimang, St (Prodi Hukum Tata Negara (Siyasah Syariyyah) Fakultas Syariah dan Hukum UIN Alauddin Makassar, 2025)
Community empowerment is an effort for the potential and capabilities of the community, so that the community can realize their identity, dignity and worth to survive and develop themselves in the social, economic, religious and cultural fields. This study aims to determine the role of the Community Empowerment Institution (LPM) in Manjapai Village, Bontonompo District, Gowa Regency. This research is a qualitative field research with research methods using observation, interviews and documentation. The results showed that the role of the Community Empowerment Institution (LPM) in Manjapai village had not been carried out optimally, members of the Community Empowerment Institution (LPM) did not understand the functions and duties of the institution they carried out. One of the causes is the lack of communication between the community and community institutions and the village government. This shows that the function of the Community Empowerment Institution (LPM) based on the Indonesian government regulation no. 72 of 205 regarding villages cannot be implemented properly. Based on the perspective of Siyasah Syariyyah, the performance of community institutions in terms of leadership for village development has not met the characteristics of good leadership. In this case, in terms of trust, members of the Community Empowerment Institution (LPM) have not been optimal in carrying out their duties or mandates given, for example uneven development, and have not continued the empowerment program that the community wants.